Prostaglandin Endoperoxides. Novel Transformations of Arachidonic Acid in Human Platelets - Hamberg, Mats (1974)
Arachidonic acid incubated with human platelets was converted into three compounds, 12L-hydroxy-5,8,10,14-eicosatetraenoic acid, 12L-hydroxy-5,8,10-heptadecatrienoic acid, and the hemiacetal derivative of 8-(1-hydroxy-3-oxopropyl)-9,12L-dihydroxy-5,10-heptadecadienoic acid. The formation of the two latter compounds from arachidonic acid proceeded by pathways involving the enzyme, fatty acid cyclo-oxygenase, in the initial step and with the prostaglandin endoperoxide, PGG(2), as an intermediate. The first mentioned compound was formed from 12L-hydroperoxy-5,8,10,14-eicosatetraenoic acid, which in turn was formed from arachidonic acid by the action of a novel lipoxygenase. Aspirin and indomethacin inhibited the fatty acid cyclo-oxygenase but not the lipoxygenase, whereas 5,8,11,14-eicosatetraynoic acid inhibited both enzymes. The almost exclusive transformation of the endoperoxide structure into non-prostaglandin derivatives supports the hypothesis that the endoperoxides can participate directly and not by way of the classical prostaglandins in regulation of cell functions. The observed transformations of arachidonic acid in platelets also explain the aggregating effect of this acid.